Komodifikasi Budaya Pria Jawa di Iklan Djarum 76 Versi “Om Jin Buat Zaskia Gotik Jatuh Cinta” - Joshua Fernando; Rustono Farady Marta (Universitas Multimedia Nusantara, 2018)
Djarum 76 is one of the leading cigarette brands in Indonesia and always actively use advertising as a means to promote their products to the public. Ad content that is often used by Djarum 76 is the figure of a light-bulb genie named